Examining gender, age, and body mass index as determinants of muscular strength and flexibility in young adults / Muhammad Iqbal Husaini ... [et al.]. - Husaini, Muhammad Iqbal; Linoby, Adam; Sazali, Razif; Zulqarnain, Muhammad; Haziq, Amrun; Md Yusoff, Yusandra (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study explores the correlation between hand-grip strength and flexibility in early adulthood. By addressing methodological gaps from prior research demographic limitations, the study aims to provide robust evidence on the relationship between these fitness components [1]. The findings could offer broader insights into their applicability as reliable predictors of physical fitness in diverse early adult populations. A convenience sample of 23 adults (aged 26–39, both genders) participated. Hand-grip strength was measured using a Camry dynamometer (model EH101) [2], and flexibility was assessed using the Sit-and-Reach Box. Participants performed three trials for each test, with the highest values recorded. Statistical analyses included descriptive statistics, Spearman’s correlation, and regression models using Jamovi, with significance set at p<0.05 to evaluate strength-flexibility relationships [3].